A Rare Case of Intraocular Adipocytic Metaplasia in a Phthisical Eye - Das, Bidhan Chandra; Das, Dipankar; Kuri, Ganesh Chandra; Deka, Apurba (Nepalese Journal of Ophthalmology, 2025)
Introduction: Phthisis bulbi is an end stage ocular disease caused by injury, long term eye disease and infection. The adipocytic metaplasia within the ocular coat is a rare variety of metaplasia. Case: An 18 year-old female presented with complaints of severe dimness of vision in the right eye for last 11 years. Observation: Slit lamp examination showed total cataract, shallow anterior chamber and enophthalmos in the right eye. As the right eye was blind, enucleation with silicon ball implant was advised. Histopathological examination of the eyeball showed evidence of phthisical eye, exudative retinal detachment with extensive osseous and adipocytic metaplasia. Conclusion: Adipocytic metaplasia of retinal pigment epithelium is a very rare feature observed in intraocular pathology.